Protocol paper: a multi-center, double-blinded, randomized, 6-month, placebo-controlled study followed by 12-month open label extension to evaluate the safety and efficacy of Saracatinib in Fibrodysplasia Ossificans Progressiva (STOPFOP) - Smilde, BJ; Stockklausner, C; Keen, R; Whittaker, A; Bullock, AN; von Delft, A; van Schoor, NM; Yu, PB; Eekhoff, EMW (BioMed Central, 2022)
Background Fibrodysplasia Ossificans Progressiva (FOP) is a genetic, progressive and devastating disease characterized by severe heterotopic ossification (HO), loss of mobility and early death. There are no FDA approved medications. The STOPFOP team identified AZD0530 (saracatinib) as a potent inhibitor of the ALK2/ACVR1-kinase which is the causative gene for this rare bone disease. AZD0530 was proven to prevent HO formation in FOP mouse models. The STOPFOP trial investigates the repositioning of AZD0530, originally developed for ovarian cancer treatment, to treat patients with FOP. Methods The STOPFOP trial is a phase 2a study. It is designed as a European, multicentre, 6-month double blind randomized controlled trial of AZD0530 versus placebo, followed by a 12-month trial comparing open-label extended AZD0530 treatment with natural history data as a control. Enrollment will include 20 FOP patients, aged 18–65 years, with the classic FOP mutation (ALK2 R206H). The primary endpoint is objective change in heterotopic bone volume measured by low-dose whole-body computer tomography (CT) in the RCT phase. Secondary endpoints include 18F NaF PET activity and patient reported outcome measures. Discussion Clinical trials in rare diseases with limited study populations pose unique challenges. An ideal solution for limiting risks in early clinical studies is drug repositioning – using existing clinical molecules for new disease indications. Using existing assets may also allow a more fluid transition into clinical practice. With positive study outcome, AZD0530 may provide a therapy for FOP that can be rapidly progressed due to the availability of existing safety data from 28 registered clinical trials with AZD0530 involving over 600 patients. Trial registration EudraCT, 2019–003324-20. Registered 16 October 2019, https://www.clinicaltrialsregister.eu/ctr-search/trial/2019-003324-20/NL. Clinicaltrials.gov, NCT04307953. Registered 13 March 2020.